Ethnobotanical plant awareness among secondary school students of Malaybalay, Philippines - Doreen Khrystel P. Gonzales; Monera A. Salic-Hairulla; Vanjoreeh A. Madale (Institute of Advanced Engineering and Science, 2026)
Plant awareness, encompassing attention, knowledge, and attitudes toward plants, are essential for fostering biodiversity appreciation and environmental stewardship. In Bukidnon, where a rich ethnobotanical heritage exists, limited research has explored students’ awareness of ethnobotanical plants, potentially undermining local conservation efforts. This study assessed ethnobotanical plant awareness among 320 secondary school students from three schools in Malaybalay, Bukidnon, using a quantitative survey design. A structured survey measured three dimensions of awareness: visual attention, knowledge/understanding, and attitudes. Data were analyzed using descriptive statistics, Mann-Whitney U, Kruskal-Wallis tests, and Spearman’s rho correlations to explore differences and relationships across gender and grade levels. Findings revealed a marked preference for animals over plants, with students demonstrating limited visual attention and knowledge regarding local ethnobotanical species. Significant differences in plant awareness were observed across grade levels, while gender differences were less pronounced. Significant relationships were found between visual perception, knowledge, and attitude which describes the multidimensional nature of plant awareness. The results highlight critical gaps in plant awareness, underscoring the need for integrative educational strategies. Incorporating local ethnobotanical knowledge into science, technology, engineering, and mathematics (STEM) curricula may enhance students’ engagement, species literacy, and environmental responsibility. Addressing plant awareness disparities among students is vital for effective biodiversity conservation and the development of future environmental stewards in Bukidnon.